Туристична регіоналізація Закарпаття - Фодор Дюло; Товт Атілла; Fodor Gyula; Tóth Attila (Вежа-Друк, 2018)
Abstract. The tourism of Transcarpathia progresses gradually in the latest decades, and this is true for the diversity of services and the quality of their rendering as well. Thus, it is more and more important to provide a professionally grounded division of the region into touristic-recreational spatial units. The importance of the present work lies in offering a possible touristic regionalization of the county,

Резюме. Туризм Закарпаття поступово набирає нові обороти, як у різноманітті послуг, так і у якості їх надання. Тому все важливішим постає питання обґрунтованого у фаховому відношенні поділу краю на рекреаційно-туристичні одиниці. Важливість цієї роботи полягає у запропонуванні можливої туристичної регіоналізації області.
Touristic Regionalization of Transcarpathia
Keywords: регіони; прикордонне співробітництво; туристичний маркетинг; туристична інфраструктура